Two Cases of Hansen's Disease - Koseki, Masamichi; Tanaka, Michi; Sugita, Yasuyuki; Horii, Noriko; Ishii, Norihisa; Ichikawa, Eiko; Otsuka, Fujio (JAPANESE JOURNAL OF LEPROSY, 2003)
We report two cases of Hansen's disease. Case 1 was 71-year old Japanese man who developed left ulnar nerve palsy since 7 years ago, multiple erythema on his body since 2-3 years ago, and erythematous nodules on his face since 3 months ago. He had no history of living outside Ibaraki prefecture. The clinical feature, the skin biopsy, laboratory data showed that he had borderline lepromatous leprosy. He was treated with multi-drug therapy which was effective and was stopped 3 years after the bacterial index showed negative. Ten months later, erythema on his body and face appeared and the therapy was restarted. Case 2 was 68-year old Japanese man who developed 5 cm of nummular erythema with slight numbness on his right forearm since 3 months ago. He had lived in Brazil since he was 24 to 64 years old. The skin biopsy showed epithelioid cell granuloma in the dermis involving vessels and nerves. Polymerase chain reaction test showed the M.leprae DNA, and he was diagnosed as indeterminate leprosy. He was treated with dapson and rifampicin and 2 months later, erythema and numbness disappeared.